The influence of the secondary electrons induced by energetic electrons impacting the Cassini Langmuir probe at Saturn. Issue 11 (15th November 2013) - Garnier, P.; Holmberg, M. K. G.; Wahlund, J.‐E.; Lewis, G. R.; Grimald, S. Rochel; Thomsen, M. F.; Gurnett, D. A.; Coates, A. J.; Crary, F. J.; Dandouras, I.
<x xml:space="preserve">Abstract</x> [1] The Cassini Langmuir Probe (LP) onboard the Radio and Plasma Wave Science experiment has provided much information about the Saturnian cold plasma environment since the Saturn Orbit Insertion in 2004. A recent analysis revealed that the LP is also sensitive to the energetic electrons (250–450 eV) for negative potentials. These electrons impact the surface of the probe and generate a current of secondary electrons, inducing an energetic contribution to the DC level of the current‐voltage (I‐V) curve measured by the LP. In this paper, we further investigated this influence of the energetic electrons and (1) showed how the secondary electrons impact not only the DC level but also the slope of the (I‐V) curve with unexpected positive values of the slope, (2) explained how the slope of the (I‐V) curve can be used to identify where the influence of the energetic electrons is strong, (3) showed that this influence may be interpreted in terms of the critical and anticritical temperatures concept detailed by Lai and Tautz (2008), thus providing the first observational evidence for the existence of the anticritical temperature, (4) derived estimations of the maximum secondary yield value for the LP surface without using laboratory measurements, and (5) showed how to model the energetic contributions to the DC level and slope of the (I‐V) curve via several methods (empirically and theoretically). This work will allow, for the whole Cassini mission, to clean the measurements influenced by such electrons. Furthermore, the understanding of this influence may be used for other missions using Langmuir probes, such as the future missions Jupiter Icy Moons Explorer at Jupiter, BepiColombo at Mercury, Rosetta at the comet Churyumov‐Gerasimenko, and even the probes onboard spacecrafts in the Earth magnetosphere.